Profit efficiency among catfish marketers in Lagos state, Nigeria: a Stochastic Profit Frontier Analysis (SPFA) approach - Settings Kazeem , Aboaba (Applied Studies in Agribusiness and Commerce, 2021)
The study analyzed the determinants of profit efficiency among catfish marketers in Lagos state, Nigeria. Multistage sampling procedure was used to select 120 catfish marketers, data were collected with the aid of a structured questionnaire. The data collected were analyzed with the use of descriptive statistics, enterprise budgetary technique, Shephered-Futrell method and stochastic profit frontier analysis (SPFA) model. The result of the gross ratio and net return on investment reveals that catfish marketing was a profitable and bankable enterprise. About 76.72% of sales revenue was taken up by the costs. The SPFA reveals that cost of catfish purchased and depreciation cost had positive (p